PENGARUH LAYANAN KONSELING INDIVIDUAL DALAM MENINGKATKAN KECERDASAN INTELEKTUAL DAN EMOSIONAL DI SMKN1 BINUANG - Suciyanti, Suciyanti; Yuliansyah, Muhammad; Auliah, Nurul (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2019)
Binuang Vocational High School 1 often found students lacking in concentration in class when the lesson took place. Based on the identification of the problem, due to lack of understanding of students in dealing with emotional students faced in the implementation of learning. For this reason, it is necessary to conduct research on the effect of personal counseling services in improving intellectual and emotional intelligence. The aim is to find out how much influence personal counseling services have on intellectual intelligence and emotional intelligence. This research was carried out on 11 August to September 2017 with a location in Binuang 1 Vocational High School. The data is collected through interviews with respondents using a questionnaire. The study sample was taken through three stages, the school level was appointed, the class determination (two classes) was appointed, and then continued with a simple random to determine 30 respondents. Data analysis using regression results of the study shows that X against Y1 F count (18,380) is greater than F table α 0,05 df 1/28 (4.20), then Ho is rejected and Ha is accepted. X against (Y2), the calculated F value (22,413) is greater than F table (4.20) so Ho is rejected and Ha is accepted. Personal counseling services affect intellectual intelligence and emotional intelligence. It was concluded that the variable personal counseling service (X) can be used as a recommended variable in estimating the variables Y1 and Y2.